Multiband Josephson effect in an atomic scale Pb tunnel junction - Maximilian Uhl; Piotr Kot; Robert Drost; Haonan Huang; Joachim Ankerhold; Juan Carlos Cuevas; Christian R. Ast (Physical Review Research)
Multiband superconductivity plays an important role in many emergent novel superconductors and has attracted great interest over the years. Various related experimental aspects have been intensely researched, but a quantitative understanding on the Cooper-pair transport remains still elusive, despite its fundamental and technological importance. We study a Josephson junction with a scanning tunneling microscope (STM), where both tip and sample are Pb, a prototypical type I two-band superconductor. We map the properties of the junction across a wide range of normal state conductances revealing in-gap features originating from multiple Andreev reflections (MARs) and the Josephson effect. We present the theoretical framework to extract the transmission through the transport channels and describe the Cooper-pair tunneling with quantitative precision through two superconducting bands. This paves the way for the understanding of increasingly complicated superconductors.